0177 Relationship Between Sleep Architecture and Age by Gender in Brazil: Baependi Heart Study. (25th May 2022) - Taporoski, Tâmara; Beijamini, Felipe; Alexandria, Shaina; Zumpf, Katelyn; von Schantz, Malcolm; Pereria, Alexandre; Knutson, Kristen
Abstract: Introduction: Sleep stage duration has been associated with age. However, few studies have examined sleep stages across adulthood in both men and women. The objective of this analysis was to describe sleep architecture across age by gender in a large cohort of Brazilian adults. Methods: This ancillary study added polysomnography (PSG) recordings to the Baependi Heart study, a prospective family-based cohort of Brazilian adults. Preliminary analyses used data from 812 participants (517 women). Sleep was staged following standard criteria. Generalized linear models were used to assess associations between age (cubic polynomial) and sleep outcomes in analyses stratified by gender. Results: Age ranged between 18 and 88 years. Mean age was 50.0 (SD = 13.3) for women and 49.9 (SD = 14.9) for men. Expected means for women at age 50 were 6.35 hours total sleep time (TST) (95% CI: 6.22, 6.48), 213.5 minutes in N2 (95% CI: 207.2, 219.9), and 75.6 minutes (95% CI: 71.9, 79.3) in REM. These were similar to expected means for men at age 50, which were 6.3 hours TST (95% CI: 6.12, 6.48), 212.9 minutes in N2 (95% CI: 204.0, 221.8), and 78.3 minutes (95% CI: 73.7, 82.8) in REM. Expected N3 at 50 years was higher in women (44.7 minutes i, 95% CI: 44.0, 45.5) than men (30.2 minutes, 95% CI: 29.4, 31.1) and WASO duration was lower for women (62.6 minutes; 95% CI: 61.7, 63.5) than for men (69.8 minutes; 95% CI: 68.5, 71.1).Non-linear relationships with age were demonstrated for N3, REM, and WASO. For example, in women there appears to be a steeper decline in N3 between approximately ages 20-40 years, a plateau until approximately 55-60 years and then another decline. Men also exhibit a steeper decline at younger ages followed by a more gradual decline that begins around 35-40 years. By contrast, TST showed a stable, linear decline with age in men and women. Conclusion: Preliminary analyses suggest that the relationship between age and some sleep outcomes differ by gender. Future analyses on the full sample will consider splines for age to investigate further these non-linear relationships. Support (If Any): 1R01HL141881